Small Acetone Sensor with a Porous Colorimetric Chip for Breath Acetone Detection Using the Flow–Stop Method - Yuto Muramatsu; Sota Watanabe; Mahiro Osada; Kohsuke Tajima; Akihiro Karashima; Yasuko Yamada Maruo (Chemosensors)
Acetone is a well-known biogas involved in lipid metabolism and is considered a potential biomarker for diabetes. However, the conventional detection methods for acetone face the limitations of large size, complex usage, and cross-sensitivity. In this study, we developed a portable device comprising a porous colorimetric acetone analytical chip composed of 2-nitrophenyl hydrazine and porous glass. The analytical chip was highly sensitive and selective for acetone because it was based on the chemical reaction between acetone and hydrazine in a nanoporous material, which provides a large surface area. The device consisted of a 450 nm laser light source and a photodiode detector with a volume of less than 40 mL. Acetone gas was measured in the atmosphere for 10 min using the developed flow–stop method. The measurable acetone concentration ranged from 0 to 6.0 ppm with a detection limit of 0.22 ppm. We successfully conducted a feasibility study using human exhaled breath and analyzed the relationship between exercise and the acetone concentration in the breath. An upward trend in exhaled acetone levels was seen post-exercise for each individual.